The Relationship Between the Level of Knowledge, Attitude, and Practice Regarding Pelvic Organ Health and the Degree of Pelvic Organ Prolapse at Dr. M. Djamil General Hospital, Padang - Peter Wijaya Sugijanto; Bobby Indra Utama; Zurayya Fadila (Fakultas Kedokteran Universitas Andalas, 2026)
Background:Pelvic organ prolapse (POP) is a disorder of pelvic floor support structures that can adversely affect women’s physical, psychological, and sexual well-being. Poor knowledge, attitude, and behavior regarding pelvic organ health may contribute to disease progression and delay appropriate management. This study aimed to determine the relationship between the level of knowledge, attitude, and practice regarding pelvic organ health and the degree of pelvic organ prolapse among patients at Dr. M. Djamil General Hospital, Padang. Methods:An analytic observational study with a cross-sectional design was conducted at the Urogynecology Clinic of Dr. M. Djamil General Hospital from January to March 2025. Ninety female patients diagnosed with POP were selected through consecutive sampling. Data were collected using a validated Knowledge, Attitude, and Practice (KAP) questionnaire and physical examination based on the Pelvic Organ Prolapse Quantification (POP-Q) system. Associations between variables were analyzed using the Chi-square test with a significance level of p<0.05. Results:Most respondents demonstrated low levels of knowledge, attitude, and practice regarding pelvic organ health. The majority experienced stage IV (severe) POP. There was a significant relationship between knowledge level and POP degree (p=0.000), and between attitude and POP degree (p=0.002). Women with poor knowledge were 8.485 times more likely to experience severe POP, while those with negative attitudes were 4.125 times more likely. No significant relationship was found between behavior and POP degree (p=0.183). Conclusion:Knowledge and attitude significantly influence the severity of pelvic organ prolapse, whereas behavior does not. Enhancing women’s awareness and education regarding pelvic health is crucial to prevent severe prolapse and improve quality of life.